MANAGEMENT OF GRAIN INFECTING FUNGI OF SORGHUM THROUGH SPRAY ON EARHEAD BY CHEMICAL AND NON CHEMICAL MEANS - GANESH S. KOTGIRE,; S. T. PATEL,; S. T. PATEL,; VIJAYKUMAR V. GITTE, (The Bioscan, 2012)
Grain infecting fungi are important constraints for the sorghum crop grown during Kharif season particularly when grain formation stage is synchronized with high field humidity, as well as when harvesting of matured earhead is delayed. Different phytoextracts, bio agents and one chemical were used for spray purpose. Three sprays of thiram @ 0.2% on earhead at an interval of 15 days starting from 50% emergence of earhead effectively reduced grain mold infection (23.3%) and thereby improved seed health status. Phytoextracts viz., Dhatura, Tulsi, Garlic and Neem 10 per cent were found promising for reducing grain mold incidence which showed only 16.9 to 21.9 per cent incidence of fungi.